THE INFLUENCE OF TAX KNOWLEDGE, UNDERSTANDING OF TAX REGULATIONS, AND IMPLEMENTATION OF E-FILLING SYSTEMS, TOWARDS MSMEs TAXPAYER COMPLIANCE WITH TAX SOCIALIZATION AS A MODERATING VARIABLE (SURVEY ON UMKM AGENCY WP REGISTERED AT KPP PRATAMA BATAM SELATAN - Silaban, Amon; Robin, Robin; Satriawan, Bambang; Irfan, Irfan; Khaddafi, Muammar; Wibisono, Chablullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to analyze and provide empirical evidence about the effect of tax knowledge, understanding of tax regulations, and the application of the e-filling system on taxpayer compliance with taxation socialization as a moderator. The population of this study is umkm corporate taxpayers registered at KPP Pratama Batam Selatan with a total population of 14,483 taxpayers. This study uses the Slovin formula to obtain a total sample of 99 taxpayers. This study uses primary data and secondary data with a quantitative approach. The primary data collection method is through a questionnaire which is measured using a Likert scale, while the secondary data is obtained from the Directorate General of Taxes through the application of e-research data. Data analysis method using Partial Least Square (PLS) with SmartPLS application. The test results show that tax knowledge has a significant effect on taxpayer compliance with a P-Value of 0.003 <0.05. Understanding of tax regulations has a significant effect on taxpayer compliance with a P-Value of 0.000 <0.05, but the implementation of the e-filling system has a significant negative effect on taxpayer compliance. Tax socialization moderates the relationship between tax knowledge and the implementation of the e-filling system on taxpayer compliance. Meanwhile, socialization of taxation does not moderate the relationship between understanding of tax regulations and taxpayer compliance. This moderating effect is called predictor moderation. Understanding of tax regulations has a significant effect on taxpayer compliance with a P-Value of 0.000 <0.05, but the implementation of the e-filling system has a significant negative effect on taxpayer compliance. Tax socialization moderates the relationship between tax knowledge and the implementation of the e-filling system on taxpayer compliance. Meanwhile, socialization of taxation does not moderate the relationship between understanding of tax regulations and taxpayer compliance. This moderating effect is called predictor moderation. Understanding of tax regulations has a significant effect on taxpayer compliance with a P-Value of 0.000 <0.05, but the implementation of the e-filling system has a significant negative effect on taxpayer compliance. Tax socialization moderates the relationship between tax knowledge and the implementation of the e-filling system on taxpayer compliance. Meanwhile, socialization of taxation does not moderate the relationship between understanding of tax regulations and taxpayer compliance. This moderating effect is called predictor moderation. socialization of taxation does not moderate the relationship between understanding of tax regulations and taxpayer compliance. This moderating effect is called predictor moderation. socialization of taxation does not moderate the relationship between understanding of tax regulations and taxpayer compliance. This moderating effect is called predictor moderation.